The innovative functions of the AI-assisted book creator in supporting teachers’ administrative and learning needs - Widyastuti, Marwanto (Majelis Pembinaan Kader Sumber Daya Insani Pimpinan Daerah Muhammadiyah Kota Salatiga, 2026)
Abstract The integration of digital authoring applications has provided new opportunities for teachers to create learning materials that are more engaging, relevant, and contextual to students’ needs. Nevertheless, in practice, many teachers have not yet fully optimized these technologies due to time constraints and limited digital literacy. This research explores the innovative functions of the AI-assisted Book Creator application in supporting both administrative and instructional needs of teachers in Semarang Regency and Salatiga who have previously participated in Book Creator training programs. This research employed a qualitative research design to capture teachers’ real-life experiences with using AI-assisted Book Creator in their daily professional practices. Data were collected through classroom observation, in-depth interviews, and analysis of administrative and teaching documents. This approach enables the researchers to obtain a comprehensive understanding of how the application was utilized, adapted, and perceived by teachers in authentic educational contexts. The findings demonstrate that AI-assisted Book Creator was perceived as useful for administrative purposes such as organizing lesson plans, creating a digital portfolio, and compiling learning reports. The application also plays an important role in helping teachers develop interactive learning materials, digital student projects, and reflective learning documents. However, the research reveals persistent challenges, including teachers’ lack of digital literacy, the limited duration of training, internet connectivity, and infrastructure constraints. This research concludes that AI-assisted Book Creator has strong potential to support teachers’ administrative and pedagogical work when accompanied by institutional support and continuous professional development. The findings are expected to inform school leaders and educators in making more effective decisions regarding the integration of digital technologies, particularly Book Creator in Educational practice. Keywords: Book Creator; Administrative needs; digital learning; educational technology.